BIOCHEMIC:AL COMPOSITION OF THE LAMELLIBRANCHS MERETRIX CASTA (CHEMNITZ) AND SANGUINOLARIA DIPHOS (GMELIN) - Wafar, M V Mohideen (Indian Journal of Fisheries, 2011)
The two eulamellibranch bivalves, Meretrix casta (Chemnitz) (Family:Veneridae) and Sanguinolaria diphos (Gmelin) (Family: Psammobiidae) arefound in Vellar estaary, Porto Novo (Lat. 11Â°29TS[ and Long. 72Â°49'E). Meretrixcasta occurs in good quantities in the estuary while Sanguinolaria diphos isfound in small numbers. Horaell (1917) pointed out that the clam Meretrixcasta "is probably the most important food mollusc of the Madras Presidency